Detecting Coastal Atmosphere Weathering Process on Andesite Rock Using Magnetic Susceptibility and Fe3O4/Fe2O3 Ratio - Siti Zulaikah; Rini Pujiastuti; Ghyfanny An Afrillah (BULLETIN OF THE MARINE GEOLOGY, 2020)
Weathering is a geological phenomenon that is often an important considered because of its destructive properties, mainly in subsurface. Many parameters are used to measure the presence of weathering indications. This study focuses on testing of magnetic susceptibility (c), compound oxide content and Fe3O4/Fe2O3 ratio that have been selected as an indicators of weathering process. This study explains in detail the quantitative analysis of weathering based on these parameters in basaltic andesite rocks found in coastal atmospheric areas. The results obtained for weathered rocks, magnetic susceptibility, compound oxide content such as CaO and the Fe3O4/Fe2O3 ratio has decreased significantly. In the coastal atmosphere, the weathering of basaltic andesite rocks also marked by the distribution of magnetic minerals which tend to be in the domain of pseudo single domain (PSD) or single domain (SD). Thus it can be concluded that both of low frequency magnetic susceptibility (clf), CaO and Fe2O3 content and also the Fe3O4/Fe2O3 ratio can be used as weathering level indicators.Keywords: weathering, andesite, magnetic susceptibility, Fe3O4/Fe2O3 ratio, coastal atmosphere. Pelapukan merupakan fenomena geologi yang sering menjadi pertimbangan penting karena sifatnya destruktif terutama pada bawah permukaan. Banyak parameter yang digunakan untuk mengukur adanya indikasi pelapukan. Penelitian ini berfokus pada pengujian suseptibilitas magnetik (c), kandungan senyawa kimia dan rasio Fe3O4/Fe2O3 yang dipilih menjadi parameter sebagai indikator pelapukan. Penelitian ini menjelaskan secara rinci analisis kuantitatif pelapukan berdasarkan kedua parameter tersebut pada batuan beku basaltik andesit yang terdapat pada area atmosfer pantai. Hasil penelitian didapatkan untuk batuan lapuk, suseptibilitas magnetik, kandungan senyawa kimia CaO dan rasio Fe3O4/Fe2O3 mengalami penurunan. Pada atmosfer pantai batuan basaltik andesit yang mengalami pelapukan juga ditandai oleh distribusi mineral magnetik yang cenderung berdomain pseudo single domain (PSD) maupun single domain (SD). Dengan demikian dapat disimpulkan bahwa baik suseptibilitas magnetik low frekuensi (clf), kandungan senyawa kimia CaO dan Fe2O3 maupun rasio Fe3O4/Fe2O3 dapat dijadikan sebagai indikator tingkat pelapukan.Katakunci: pelapukan, andesite, suseptibilitas magnetik, rasio Fe3O4/Fe2O3, atmosfer pantai.